2013
DOI: 10.1111/1541-4337.12032
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Novel Protein Sources (Insects, Microalgae, Seaweed, Duckweed, and Rapeseed) and Legislative Aspects for Their Application in Food and Feed Production

Abstract: Novel protein sources (like insects, algae, duckweed, and rapeseed) are expected to enter the European feed and food market as replacers for animal-derived proteins. However, food safety aspects of these novel protein sources are not well-known. The aim of this article is to review the state of the art on the safety of major novel protein sources for feed and food production, in particular insects, algae (microalgae and seaweed), duckweed, and rapeseed. Potential hazards for these protein sources are described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
179
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 423 publications
(213 citation statements)
references
References 134 publications
3
179
0
3
Order By: Relevance
“…However, the price of soybean Values are average from duplicate groups of samples a Diets represent; control (without black soldier fly larval meal inclusion), BSFL25 (25%), BSFL50 (50%), BSFL75 (75%) and BSFL100 (100% fish meal replacement using black soldier fly larval meal) meal and other plant feedstuff has also increased dramatically due to their growing demand for the direct human consumption (FAO 2009). Therefore, attention could be directed towards the locally available and cheaper protein source, which may create flexibility in diet formulations and insect meal has been identified as one such ingredient (Rumpold and Schlüter 2013;Van der Spiegel et al 2013;Van Huis 2013;Lock et al 2015). Black soldier fly was early been recognized as the potential candidate ingredient due to its rich nutritional profile comprised of 40% protein and 35% lipid (Bondari and Sheppard 1987).…”
Section: Discussionmentioning
confidence: 99%
“…However, the price of soybean Values are average from duplicate groups of samples a Diets represent; control (without black soldier fly larval meal inclusion), BSFL25 (25%), BSFL50 (50%), BSFL75 (75%) and BSFL100 (100% fish meal replacement using black soldier fly larval meal) meal and other plant feedstuff has also increased dramatically due to their growing demand for the direct human consumption (FAO 2009). Therefore, attention could be directed towards the locally available and cheaper protein source, which may create flexibility in diet formulations and insect meal has been identified as one such ingredient (Rumpold and Schlüter 2013;Van der Spiegel et al 2013;Van Huis 2013;Lock et al 2015). Black soldier fly was early been recognized as the potential candidate ingredient due to its rich nutritional profile comprised of 40% protein and 35% lipid (Bondari and Sheppard 1987).…”
Section: Discussionmentioning
confidence: 99%
“…The exception is aquaculture; in October 2013 the EU allowed the use of non-ruminant proteins as feed for farmed fish (Van der Spiegel et al, 2013). However, strict slaughterhouse requirements that were not written with insect breeding in mind have hindered the development of this market.…”
Section: Eu Policy On Insects As Food and Feedmentioning
confidence: 99%
“…The limits to human and livestock consumption involve safety issues, the main concerns being heavy metals, toxic chemicals, allergens, and pathogens (Van Huis, 2015;Van der Spiegel et al, 2013). However, recent research of fly larvae in animal feed indicated that "with appropriate quality assurance mechanisms and testing regimes in place to monitor chemicals in the larvae then we can conclude that it is feasible to produce fly larvae that are free from chemicals of concern to the animal feed sector" (Charlton et al, 2015, p. 15).…”
Section: Eu Policy On Insects As Food and Feedmentioning
confidence: 99%
See 1 more Smart Citation
“…However, so far, little attention has been paid to the legal aspects of introducing edible insects. The existing studies on legal aspects of food security refer to the old EU legislation on the so-called novel foods, but they do not reflect its updated wording adopted in late 2015 (Belluco 2013;Rumpold 2013;van der Spiegel 2013). Food security has been addressed particularly with respect to developing countries ( Jeníček and Grófová 2015a, b).…”
mentioning
confidence: 99%